India and Its Television: Ownership, Democracy, and the Media Business. (May 2015) - Mehta, Nalin
With annual revenues of about 17 billion in 2012, India is among the world's top 15 global media and entertainment markets. While much attention has been focused in recent years on India's rise as an emerging economy, its great-power potential as the world's largest democracy and the future trajectory of its growth but the role of India's burgeoning media industry in this wider story is much less understood. For a country with the world's largest newspaper market, second largest telecommunications market, third largest television market and second largest Facebook community, the virtual absence of India from most mainstream global communications studies within academia is strange. In revenue terms, India's share of the global media sector still remains small but within the top 15 media and entertainment economies, only India has had consistent over-15 percent growth rates for years. Yet, outside of India, within the wider ambit of policy and international relations, few understand the crucial role Indian media play in the ebbs and flows of Indian politics and how central it is to India's boisterous democracy. This article concentrates on Indian television and its future directions. Combined with the rise of the other device that has grown faster than toilets in India—the mobile phone—television has fundamentally reshaped Indian democracy and emerged as a critical social lever. This article outlines ownership patterns in Indian television, the divergences and commonalities across regional languages and what this means for India's democracy.